Internship report on the procurement process of united groups ‘IPCO Development & Hotels Limited - Sarwar, Md. Ishtiak (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.